Enhancing Civic Education Outcomes of Fifth Grade Students through the Make a Match Cooperative Model at MIS Persiapan Negeri Namlea - Sundu, Nur Santi; Saimima, Raihana; Latukau, Jubaid (Sinergi International Journal of Education, 2025)
This study addresses the issue of inadequate learning outcomes in Civics among fifth-grade students at MIS Persiapan Negeri Namlea, Buru Regency. The research aimed to explore the effectiveness of the Make a Match cooperative learning model in improving students' Civics learning outcomes. A qualitative research approach was employed, using classroom action research (CAR) methodology, which involved iterative cycles of planning, implementation, observation, and reflection. The participants were 48 fifth-grade students (27 boys and 21 girls). Data collection methods included observations, tests, and summaries. Data analysis was conducted through data reduction, presentation, and conclusion drawing. The findings showed a significant improvement in student engagement and learning outcomes. In Cycle I, only 35.41% of students met the Minimum Completeness Criteria (KKM), while in Cycle II, 81.25% of students achieved the KKM, demonstrating the effectiveness of the Make a Match model in enhancing student learning outcomes.